Big Data dan Perawatan Kesehatan Studi Awal Menuju Perawatan Kesehatan Masa Depan - William Aprilius (Universitas Multimedia Nusantara, 2015)
The development of database technology makes a variety of data and medical information is stored in digital form and present in the form of big data. Currently, healthcare that utilizes big data is still in the development stage. Big data starts to be used to expand insight and improve the quality of healthcare. This paper provides information related to the integration of big data in healthcare. Source for big data in healthcare is presented. Opportunities, impacts, and challenges in the integration process of big data in healthcare are also described. Index Terms - big data, healthcare